Perception, Attitude And Preparation For Aged Society In Thailand Among People In Bangkok - Suvanno S. (2023)
This quantitative research explores the perception, attitude, and preparation for an aged society (AS) in Thailand among the Bangkok people. The questionnaires were used to collect data from 420 samples. The t-test, ANOVA, and Pearson's Product Moment Correlation Coefficient were used to examine the hypotheses. The result showed that the samples had a high perception, attitude, and preparation for AS in Thailand. The findings also revealed that people of different ages, incomes, and family types have different perceptions of AS in Thailand at the significant level of 0.05; there is no significant difference in gender and education. People of different gender, ages, income, and family type have different attitudes toward AS and preparation for AS in Thailand at the significant level of 0.05; there is no significant difference in education. The perception of AS in Thailand and the attitude toward AS in Thailand positively correlate with the preparation for AS in Thailand at the statistically significant level of 0.01.